Ubiquitous learning in focus: a scientific view of Dentistry content on YouTube and Facebook - pilot study (Research, Society and Development, 2021)
With the emergence of the internet, the act of transmitting information has been going through transition and becoming ever faster, as a result, electronic resources and digital platforms have been gradually added to daily life, and thus modifying the way individuals act, even affecting the academic dental scenario. The aim of this study is to characterize the potential of YouTube and Facebook as active technological teaching-learning tools in dentistry, analyzing the academic and scientific reliability of the contents available on the platforms. To carry out this work, firstly, a literature review was carried out as the basis of the research, and later structured questionnaires with objective questions were developed and applied in each of the platforms under study, to analyze the academic contents that are being broadcast. The results show that 100% of the analyzed material on Facebook has references in their publications, whereas on YouTube only 55% of the channels have an explicit scientific basis, but the survey also revealed the more commercial character of Facebook, given most of the page properties evaluated in this social network, be business. This research was able to emphasize that digital platforms are improving their quality and increasing the level of scientific reliability, however, if these surveys were done, as the algorithm limited the sample number, in this way multidirectional searches can be applied in order to cover a larger number of channels and pages on social networks.